Teachers' Perceptions toward Student Worksheets Based on Sugarcane Waste Treatment Projects to Improve Students' Creative Thinking Skills - Abida, Rahma; Fadiawati, Noor; Setyarini, M. (FKIP Universitas Lampung, 2022)
This study aims to describe teachers’ perceptions towards students’ worksheets based on bagasse waste processing projects to improve students' creative thinking skills. This research was conducted in Lampung Province involving 42 junior high school science teachers. This study uses the ADDIE research and development method by Branch. At the analysis stage, performance analysis and needs analysis are carried out. At the development stage, two education experts validated the suitability of the content with project-based learning steps and indicators of creative thinking skills according to Torrance and validated the suitability of the construction with the components of the student worksheets. At the implementation stage, it will be tested in class VII at SMP Negeri 3 Kotabumi. The evaluation stage is by evaluating the results of students after the learning is carried out. The success of increasing students' creative thinking skills is seen based on the results of n-gain and effect size.Keywords: students’ worksheet, project based learning, creative thinking skills.DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp335-344